#TITLE_ALTERNATIVE# - SUJATMIKO (NIM 23305005), WAHYU
This research was intended to observe more thoroughly about human thermal comfort in natural air-ventilated building in Indonesia: Bandung, Bekasi, Surabaya, and Semarang. This study was conducted to acquire more information concerning the occupants' thermal neutrality, acceptability and preference, and adaptive behavior in order to find thermal comfort. The collected subjects' thermal votes was compared to the ASHRAE 55-2004 Adaptive Comfort Standard. The result was compared to the PMV-PPD static comfort model, which is adopted by ISO 7730-2005 and ASHRAE 55-2004 and with the other static comfort models (ET*, SET*, DISC, TSENS, dan HSI) as well. From the analysis of the subjects' actual votes it can be pointed out that the thermal preference result of the acclimatized subjects that were doing constant sedentary activity (1 -1.2 met) is lower than its thermal neutrality. Thermal neutrality was occurred in outdoor parameter: T db = 27.1 degrees C; indoor parameters: Tdb = 27.3degrees C, Top = 27.4 oC, ET* = 29.4 degrees C, SET* = 30.1 degrees C, DISC = 1.7, TSENS = 1.1, PMV = 1.1, and HSI = 44.8. Thermal preference was occurred in outdoor parameter: Tdb = 24.5 degrees C; indoor parameters Tdb = 25. 3 degreesC, Top = 25. 5 degrees C, ET* = 27.3 degrees C, SET* = 27. 2 degrees C, DISC = 0.8, TSENS = 0.7, PMV= 0.5 and HSI = 25. From the analysis of mean regression it can be showed up that the subjects' actual rate thermal sensitivity, neutrality and preference were laid in Top value, which is higher than the static model predicted result. The actual thermal preference votes were laid in Top = 27.7 oC, while the DISC prediction occurred in Top = 21.1 degrees C, the TSENS prediction occurred in Top = 21.3 oC, and the PMV prediction occurred in Top = 23. 8 degrees C. According to the HSI prediction neutrality should occurred in Top = 17.71 degrees C, but in reality the subjects' actual neutrality votes occurred in Top 27.4 oC and preference in 23.2 degrees C. The ET* and SET* thermal neutralities were occurred in Top = 27.8 degrees C and 27.5 degrees C respectively, but on the contrary the subjects' preference were in Top 25.6 degrees C and 24.4 degrees C respectively. From the analysis result of the thermal acceptability it can be pointed out that the range of the subjects' accepted temperatures were laid between Top = 22.830.2 degrees C or between ET* = 23.4-32.3 degrees C. This is somehow in accordance with the 80% comfort zone of the ASHRAE 55-2004 adaptive comfort standard. From the investigation of the Bandung and Bekasi residents' adaptive behavior, it can be showed up that the subjects were in general not completely satisfied with their house surrounding's condition. They were not wholly utilizing those passive controlling facilities (windows, doors, room-design in the building, roof material) and the availability of their outdoor garden as a controlling facility to satisfy the occupants' thermal comfort. According to the outlook of the quantity rate and the difference from the room thermal values, it can be figured out that the building thermal performance of the Antapani Bandung's home residences were considerably better than the other two residences: Turangga Bandung and Perumnas Bekasi. In the other side, the building thermal performance of the Perumnas Bekasi residences was considered better than the Turangga Bandung residences. The effects of climate differences, subjects' acclimatization, measuring spots, ages,gender, and even the repeating effect in answering their thermal votes in the thermal questionnaires were all observed thoroughly in this research as well.